Protokol pemikiran verbal dalam pemahaman bacaan teks bahasa Melayu (Jurnal Bahasa, 2005)
Reading and understanding the material of an academic text is a prob-lem to certain students due to their difficulties in searching vocabulary related to a term or loan word and problem in lexical processing. There-fore, this study is conducted to identify lexical processing method and second language positive transfer in reading comprehension from Form 4 students. The findings were elicited from think aloud protocol and oral retelling data. The think aloud protocol and oral retelling data were recorded, transcribed verbatim before analysed. The study was conducted on six Form 4 students from SMK Dato ' Hj. Mohd. Redza, Jalan Sikamat, Seremban. Two groups were formed based on high and low academic achievement. An article entitled, "Kaji Kandungan Program TV Tempatan" (Analysing the Content of Local TV Programmes) is used as a reading comprehension text for think aloud protocol. The study shows the presence of second language positive transfer, that is the transfer of English word meaning knowledge into Malay language. The second language positive transfer is identified from the use of translation, transfer of word meaning knowledge and contextual clues, as shown by the students when processing reading comprehension text. The student's achievement in reading comprehension ability is rather low and finding also shows that academic achievement does not de-termine the students ' reading comprehension mastery.